Advaita Brahmajñāna (Kesatuan Ātman Dengan Brahman) (Kajian Teo-Filosofi) - Putu Dana Yasa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The Advaita Brahmajñāna is one of the teachings conveyed in the Agni Purana. This knowledge is knowledge that gives human beings awareness that all the elements in this universe are ātma, and ātma is Brahman itself. Ātma and Brahman are inseparable entities, ātma gives life to every existing being and is entirely the intervention of Brahman himself. Advaita Brahmajñāna is a science that explains how humans are able to improve their quality so that they can manifest the existence of ātma in themselves. Realizing that all existing beings are Brahma or God is the pinnacle of human level to manifest the existence of God.